SOSIALISASI APLIKASI NELAYAN PINTAR (NELPIN) MELALUI PEMANFAATAN POTENSI NELAYAN DI KEL. PUNDATA BAJI - Thaha, Salmiyah; Sangkala, St. Fatimah; Asmawiyah, Asmawiyah (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2024)
This socialization aims to increase public knowledge about the development of information media in the digital era. Currently, people in Pundata Baji Village are not used to using applications to do or remind them of the work they have to do. In this community service activity the author will introduce the smart fishing application. Before downloading the application, make sure you have a fisherman's card. In general, socialization participants do not have fisherman cards. The function of the fisherman's card is to make it easier to get assistance because fishermen are already registered in the database, ensuring subsidized fuel and so on. By socializing the application as an information medium, it is hoped that participants will be able to better understand the learning materials and be able to apply the smart fishing application media.